88 The relationship between upper and lower limb function in a cohort of children with Charcot-Marie-tooth disease. (30th November 2020) - Milev, Evelin; Laura, Matilde; Rand, Sarah; Walk-Ley, Melissa; Wolfe, Amy; Rye, Catherine; Reilly, Mary; Muntoni, Francesco
Abstract : Charcot-Marie-Tooth (CMT) is a progressive disease with clinical signs presenting first in the distal lower extremities. Upper limb function in this population is also affected at a later stage of life but it is poorly researched and little is known about hand function limitations and loss of manual dexterity. The purpose of this study is to investigate the possible relationship between upper and lower limb function in a group of children and adolescents. The CMT natural history study at Great Ormond Street Hospital in London has been collecting longitudinal data of more than 120 children and adolescents with CMT (age range 4 to 21 years). Eighty one children with CMT type 1 (53% CMT1A), 22 with type 2 and 21 with other types of CMT have been assessed up to date. To evaluate upper limb function we used myometry, functional dexterity test and 9 hole peg test; to measure lower limb function the 6 minute walk test, long jump and plantar and dorsiflexion strength tests. In this study we will use correlation analysis to explore the concordance between the upper and the lower limb function. A comparison will be made between children and adolescents with demyelinating CMT and those with axonal CMT, and also individual genotypes, to look if variation in genetic subtype affects individuals in different ways. In our analysis we will assess longitudinally the correlation between upper and lower limb function in children with different subtypes of CMT. If a strong relationship between the two is found in individual conditions, we will assess further the predictive model of loss of function between upper and lower limbs in different genetically defined conditions. This study is a part of a MSc project being undertaken at UCL and a full report and results will be presented later in the year.